2021
DOI: 10.2147/jpr.s299135
|View full text |Cite
|
Sign up to set email alerts
|

Arthroplasty for Treating Traumatic Metacarpophalangeal Joint Defects: A Retrospective Study Over Three Years

Abstract: Background: Bone loss at the metacarpophalangeal joint (MCP) after trauma is difficult to treat. Objective: We aimed to investigate the effectiveness of Swanson's arthroplasty and the reason for implant fracture. Methods: We retrospectively analyzed the data of 175 patients who underwent emergency MCP arthroplasty between 2013 and 2016. Some patients used a orthosis to limit the radioulnar movement of the metacarpal joint for eight weeks after surgery (Group A), while the other patients underwent only hand reh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Recently, researchers in the People's Republic of China found that Swanson's arthroplasty is useful for treating bone loss at the metacarpophalangeal (MCP) joint after trauma. (See Xie et al, 2021. )…”
mentioning
confidence: 99%
“…Recently, researchers in the People's Republic of China found that Swanson's arthroplasty is useful for treating bone loss at the metacarpophalangeal (MCP) joint after trauma. (See Xie et al, 2021. )…”
mentioning
confidence: 99%